Mast cell - tumor cell interaction related gene and microRNA expression profiles in oral squamous cell carcinoma - Khromov, Tatjana; Sitte, Maren; Salinas, Gabriela; Schminke, Boris; Fischer, Andreas; Schliephake, Henning; Brockmeyer, Phillipp (Frontiers in Oncology, 2025)
BackroundMast cells (MCs) play a crucial role in the tumor microenvironment (TME) of oral squamous cell carcinoma (OSCC), significantly impacting patient prognosis. This study aimed to investigate the gene and microRNA (miRNA) expression profiles of MCs and OSCC cells following co-culture, providing valuable insights into the molecular background of their functional interactions.MethodsThe human OSCC cell line PCI-13 and the human MC cell line LUVA were initially cultured separately under identical experimental conditions and subsequently co-cultured for 48-72h. Transcriptome analysis of differentially expressed genes (DEGs) and sequencing of differentially expressed miRNAs were performed and analyzed using bioinformatics tools. Additionally, key genes and miRNAs identified in OSCC were assessed for their prognostic relevance in head and neck tumors using freely available online databases.ResultsThe analyses revealed distinct DEG profiles between OSCC cells and MCs under monoculture and co-culture conditions. Notable findings include DEGs involved in chemokine signaling - particularly the CCL2/CCR2 axis - TGF-β signaling, toll-like receptor (TLR) expression, and key intracellular pathways such as PI3K/Akt, JAK/STAT, Ras/Raf/MAPK, and IP3 in both cell types. Additionally, specific miRNAs, including miR-142, miR-146a, and miR-223 in tumor cells, as well as miR-381 and miR-379 in MCs, exhibited significant differential expression, highlighting their potential involvement in regulating MC-OSCC interaction. Notably, the expression levels of CCR2, along with miR-142, miR-146a, and miR-223, were identified as prognostically relevant in patients suffering from head and neck tumor.ConclusionsThe data highlight the complex and dynamic interplay between MCs and OSCC, driven by key signaling pathways and miRNA regulation. These findings provide a foundation for future functional studies and the possible development of targeted therapies aimed at modulating MC-OSCC interaction within the TME.